Foreword - Nagy, Erica; Timár, Judit (European Spatial Research and Policy, 2018)
The idea of this special issue was inspired by two powerful processes that encompassed academic studies focused on socio-spatial inequalities within Central and Eastern Europe (CEE) and beyond.